Where on Earth has our water come from? - Leeuw, N.; Catlow, C.; King, H.; Putnis, Andrew; Muralidharan, K.; Deymier, P.; Stimpfl, M.; Drake, M. (The Royal Society of Chemistry, 2010)
The presence of water in the Earth has long been an enigma. However, computer modelling techniques have shown that the adsorption of water onto the fractal surfaces of interplanetary dust particles, which are present in the planetary accretion disk, is sufficiently strong to provide a viable origin of terrestrial water. © 2010 The Royal Society of Chemistry.